'I've put diabetes completely on the shelf till the mental stuff is in place'. How patients with doctor-assessed impaired self-care perceive disease, self-care, and support from general practitioners. A qualitative study - Mads Aage Toft Kristensen; Ann Dorrit Guassora; Anne Beiter Arreskov; Frans Boch Waldorff; Bibi Hølge-Hazelton (Taylor & Francis Group, 2018)
Objective: This paper investigated patients' experiences of disease and self-care as well as perceptions of the general practitioner's role in supporting patients with impaired self-care ability. Design: Qualitative interviews with 13 patients with type 2 diabetes, concurrent chronic diseases, and impaired self-care ability assessed by a general practitioner. We analyzed our data using systematic text condensation. The shifting perspectives model of chronic illness formed the theoretical background for the study. Results: Although most patients experienced challenges in adhering to recommended self-care activities, many had developed additional, personal self-care routines that increased wellbeing. Some patients were conscious of self-care trade-offs, including patients with concurrent mental disorders who were much more attentive to their mental disorder than their somatic diseases. Patients' perspectives on diseases could shift over time and were dominated by emotional considerations such as insisting on leading a normal life or struggling with limitations caused by disease. Most patients found support in the ongoing relationship with the same general practitioner, who was valued as a companion or appreciated as a trustworthy health informant. Conclusion: Patient experiences of self-care may collide with what general practitioners find appropriate in a medical regimen. Health professionals should be aware of patients' prominent and shifting considerations about the emotional aspects of disease. Patients valued the general practitioner's role in self-care support, primarily through the long-term doctor-patient relationship. Therefore, relational continuity should be prioritized in chronic care, especially for patients with impaired self-care ability who often have a highly complex disease burden and situational context.Key points   Little is known about the perspectives of disease and self-care in patients with a doctor-assessed impaired ability of self-care.   • Although patients knew the prescribed regimen they often prioritized self-care routines that increased well-being at the cost of medical recommendations.   • Shifting emotional aspects were prominent in patients' considerations of disease and sustained GPs' use of a patient-centred clinical method when discussing self-care.   • Relational continuity with general practitioners was a highly valued support and should be prioritized for patients with impaired self-care.